Adsorbent suitable for ultra-low-concentration carbon dioxide capture and formed through hot flat plate vulcanization phase separation and preparation and application of adsorbent
The adsorbent prepared by thermal flat plate vulcanized phase separation technology solves the problems of insufficient selectivity and low adsorption capacity of ultra-low concentration carbon dioxide capture in the prior art, achieves high-efficiency and low energy consumption carbon dioxide capture, and maintains good performance in a high-humidity environment.
Patent Information
- Application Number
- CN202510067857.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The prior art has problems such as insufficient selectivity, low adsorption capacity, high energy consumption and poor humidity resistance in ultra-low concentration carbon dioxide capture concentrations.
The adsorbent is prepared by hot plate vulcanizing phase separation technology. The adsorbent is prepared by preheating the diluent, adding inert carrier and active adsorption components to form a cast film liquid, and the sulfurized plate is heat-pressed on the vulcanized plate, and finally ion exchange treatment is performed in the carbonate solution to obtain an adsorbent with high porosity and adsorption capacity.
It significantly improves the kinetic performance, adsorption capacity and porosity of the adsorbent, improves the capture efficiency of ultra-low concentrations of carbon dioxide, and maintains good adsorption performance in high humidity environments.
Smart Images

Figure CN119657099A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of direct capture of carbon dioxide from air, and in particular to a hot flat plate vulcanization phase separation molded adsorbent suitable for capturing ultra-low concentration carbon dioxide, and a preparation method and application thereof. Background Art
[0002] As global climate change intensifies, the capture and utilization of carbon dioxide (CO2) has become an important technical path to address climate issues. In existing technologies, ultra-low concentration CO2 capture (such as direct capture of air carbon dioxide, etc.) faces problems such as insufficient selectivity, low adsorption capacity, and high energy consumption.
[0003] Chemical adsorption is one of the most widely used technologies at present. For example, amine adsorbents are widely used because of their high selectivity for CO2, but they have problems such as strong corrosiveness, high energy consumption, and difficulty in regeneration.
[0004] The physical adsorption method is represented by molecular sieves and activated carbon. These materials adsorb gas through their pore structure, but their pore distribution is uneven and their adsorption kinetics are poor, especially when dealing with ultra-low concentrations of CO2 in the air, they exhibit the defect of low adsorption efficiency.
[0005] In recent years, the development of composite adsorption materials has provided a possible solution to the above problems. For example, metal organic frameworks (MOFs) materials have attracted extensive attention in the field of gas adsorption due to their high specific surface area and adjustable pore structure. Li et al. (Li J.R., Kuppler RJ, Zhou HC Selective gas adsorption and separation in metal-organic frameworks [J]. Chemical Society Reviews, 2009, 38 (5): 1477-1504.) achieved efficient gas selective separation by synthesizing MOFs with different structures.
[0006] However, MOFs materials have significant deficiencies in preparation cost, moisture resistance and chemical stability, which limit their practical application. In order to overcome these technical bottlenecks, thermal induced phase separation (TIPS), as an emerging polymer material preparation technology, has been gradually developed in the preparation of porous adsorbent materials in recent years. Zhang Jun et al. (Zhang Jun, Wang Xiaolin, Luo Feng. Preparation of low-density polyethylene microporous membrane by thermal induced phase separation [J]. Polymer Materials Science and Engineering, 2004, 20 (1): 174-178.) successfully prepared low-density polyethylene microporous membranes with high porosity and specific surface area through TIPS technology, proving that this method can generate a uniform pore structure through polymer dissolution, phase separation and extraction processes, thereby significantly improving the diffusion performance and adsorption efficiency of the adsorbent material.
[0007] Although TIPS technology has shown superior performance, the traditional TIPS process often requires high temperature (>200°C). This high temperature condition not only leads to a significant increase in process energy consumption, but may also cause the degradation of active adsorption components (such as styrene-based strong alkaline anion exchange resins), thereby reducing the adsorption performance and chemical stability of the adsorbent. In addition, porous materials generally have the problem of reduced adsorption performance in high humidity environments. For example, amine adsorbents are prone to water absorption and failure under high humidity conditions, which further limits their application in practical scenarios. Therefore, it has become an important technical requirement to develop a low-temperature and efficient preparation process and prepare adsorbents with high porosity, high adsorption capacity and excellent moisture resistance. Summary of the invention
[0008] In view of the above-mentioned technical problems and the shortcomings in the art, the present invention provides a hot flat plate sulfurized phase separation molded adsorbent suitable for ultra-low concentration carbon dioxide capture, and a preparation method and application thereof.
[0009] The specific technical solutions are as follows:
[0010] [1] A method for preparing a hot flat plate sulfurized phase separation molded adsorbent suitable for ultra-low concentration carbon dioxide capture, comprising:
[0011] Preheating the diluent, adding the inert carrier, dissolving to form a uniform solution, and then adding the active adsorption component and mixing to form a casting solution;
[0012] The casting liquid is placed on a vulcanized plate, hot pressed, then taken out and placed in a cooling bath to cool and set. The obtained membrane is soaked in an extractant to remove the diluent, and finally the membrane is soaked in a carbonate solution (such as sodium carbonate, etc.) until the ion exchange is completed to obtain an adsorbent.
[0013] In some embodiments, the diluent may include at least one of diphenyl ether, paraffin oil, toluene, and xylene, preferably diphenyl ether. Under preferred conditions, the adsorbent obtained has a higher carbon dioxide adsorption capacity and adsorption efficiency, good mechanical properties, and no volatility or toxicity problems.
[0014] In some embodiments, the preheating temperature of the diluent may be 90-150°C.
[0015] In some embodiments, the inert carrier may include at least one of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE), preferably including low-density polyethylene. Under preferred conditions, the adsorbent obtained has higher carbon dioxide adsorption capacity and adsorption efficiency.
[0016] In some embodiments, the low density polyethylene may have a melting point of 105-115°C.
[0017] In some embodiments, the linear low density polyethylene may have a melting point of 115-125°C.
[0018] In some embodiments, the high density polyethylene may have a melting point of 130-137°C.
[0019] The active adsorption component of the present invention can adopt existing technology. In some embodiments, the active adsorption component can include active adsorption resin, and the active adsorption resin can include at least one of D290 series, D201 series, D202 series, IRA-900 series macroporous resin, 201*7 series, HPR4800CL gel-type anion exchange resin, etc.
[0020] In some embodiments, the active adsorption component may be washed with a pretreatment solvent and then dried before use. Further, the pretreatment solvent may include at least one of deionized water, sodium carbonate solution, sodium hydroxide solution, hydrochloric acid solution, and ethanol.
[0021] In some embodiments, the active adsorption component can be added in the form of particles. Further, the particle size of the active adsorption component particles can be 30 to 200 microns, preferably 50 to 80 microns.
[0022] In some embodiments, the time for adding the active adsorption component and mixing can be 4 to 8 hours.
[0023] In some embodiments, based on the mass of the diluent being 100%, the mass of the inert carrier may account for 10% to 15%, and the mass of the active adsorption component may account for 20% to 25%, such as 22.5%.
[0024] In some embodiments, additive components may be added to the casting solution.
[0025] In some embodiments, based on 100% by mass of the diluent, the mass proportion of the additive component may be 5% to 15%.
[0026] In some embodiments, the additive component may include one or more of an antioxidant component, a hydrophobic functional additive, and an antistatic additive.
[0027] In some embodiments, the antioxidant component may include at least one of tetrakis(methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)methane and tris(2,4-di-tert-butylphenyl)phosphite.
[0028] In some embodiments, the hydrophobic functional additive may include at least one of polyvinylidene fluoride and polyvinyl fluoride. The weight average molecular weight of the polyvinylidene fluoride may be 180,000-534,000 g / mol. The number average molecular weight of the polyvinyl fluoride may be 50,000-120,000 g / mol.
[0029] In some embodiments, the antistatic additive may include at least one of N,N-bis(2-hydroxyethyl)-N-(3′-dodecyloxy-2′-hydroxypropyl)methylammonium methyl sulfate and stearyltrimethylammonium chloride.
[0030] In some embodiments, the temperature of the hot pressing may be 80-130° C., such as 105° C.
[0031] In some embodiments, the hot pressing pressure may be 4-20 MPa, such as 10 MPa.
[0032] In some embodiments, the heat pressing time may be 5 to 60 minutes.
[0033] In some embodiments, the temperature of the cooling bath may be 0 to 60°C, for example, 0°C, 20°C, 40°C, 60°C, etc., preferably 10 to 30°C, further preferably 15 to 25°C, and further preferably 20°C. Under preferred conditions, the adsorbent obtained has higher carbon dioxide adsorption capacity and adsorption efficiency.
[0034] In some embodiments, the thickness of the membrane may be 0.2-2 mm.
[0035] In some embodiments, the extractant may include at least one of ethanol, methanol, and cyclohexane, preferably cyclohexane. Under preferred conditions, the adsorbent obtained has a higher carbon dioxide adsorption capacity and adsorption efficiency.
[0036] [2] The adsorbent prepared according to the preparation method described in [1].
[0037] In some embodiments, the BET specific surface area of the adsorbent is greater than 9 m 2 / g, porosity greater than 60%, total pore volume greater than 0.5cm 3 / g.
[0038] [3] Use of the adsorbent according to [2] in capturing carbon dioxide. Furthermore, the adsorbent can be used for direct capture of carbon dioxide from air.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention adopts a combination of hot plate vulcanization and thermally induced phase separation technology to prepare the adsorbent. Styrene-based macroporous strong alkaline anion resin and the like are used as active adsorption components, and a porous structure is formed by dissolution-extraction phase separation of polymer materials. The kinetic properties, adsorption capacity and porosity of the adsorbent are significantly improved by optimizing the processing temperature and steps. The adsorbent can show excellent adsorption capacity and good mechanical properties in capturing ultra-low concentration carbon dioxide in the air, and can be used for environmental governance and industrial gas separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the infrared spectrum of the porous composite adsorbent sample of Example 1.
[0042] Figure 2 This is a scanning electron microscope (SEM) photograph of the porous composite adsorbent sample of Comparative Example 1.
[0043] Figure 3 This is a SEM photograph of the porous composite adsorbent sample of Example 1. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0045] Adsorption experiment: The experiment first conducts an airtightness check. After closing some valves, the device is purged with nitrogen and the concentration of carbon dioxide is monitored using an infrared analyzer. When the concentration drops to an extremely low value, a certain amount of carbon dioxide is injected and the leakage rate is observed to evaluate the airtightness of the device. Then enter the purge stage, place the desorbed material in a constant temperature sealed box, adjust the temperature and use a nitrogen purge system to ensure that the concentration of carbon dioxide and water vapor in the box reaches an extremely low level, and confirm that the adsorbent material is in a blank state without external interference. Finally, the test stage is carried out. Carbon dioxide is injected to make the gas concentration in the test environment reach the target value (air carbon dioxide concentration, i.e. 400ppm), monitor the change of carbon dioxide concentration in the adsorbent material, and repeat the above process many times until the final environmental gas concentration approaches 400ppm, which can confirm that the adsorbent material is in a saturated state.
[0046] Desorption experiment: The experiment first conducts an airtightness check, which is consistent with the previous steps and will not be repeated here. Then enter the purge stage, place the fully adsorbed saturated porous composite adsorption material in a transparent closed test box in a constant temperature test chamber, and adjust the temperature and use nitrogen to purge to ensure that the carbon dioxide concentration in the test environment drops to an extremely low level. Finally, in the test phase, switch to humidified nitrogen to pass into the test box, monitor the changes in carbon dioxide and water vapor concentrations, until the carbon dioxide concentration at the outlet drops to an approximate blank value, confirming that the carbon dioxide in the adsorption material has been completely desorbed, and the experiment ends immediately.
[0047] Comparative Example 1:
[0048] Traditional hot pressing method: First, the D290 resin particles are alkali washed, acid washed, and alcohol washed with sodium carbonate solution, dilute hydrochloric acid, and ethanol, respectively, rinsed with deionized water and dried, and then ultrafinely crushed and screened to obtain 50-80μm D290 resin powder. Subsequently, 15g LDPE particles are slowly added to a 135℃ internal mixer. When the particles are completely melted into a transparent colloid, 22.5g resin powder is slowly added. After the system is evenly mixed, the internal mixer is turned off and the mixed rubber is taken out. The mixed rubber taken out from the internal mixer is preheated to a surface temperature of 80℃ and placed on a double-roll open mill. The open mill is started and the mixed rubber is pressed into a thick sheet of about 3mm in thickness. After cooling to room temperature, the open mill is used again to roll the mixed rubber into a 0.4-1mm thick sheet, and cut into the size of 5cm×5cm required for the test, and repeatedly soaked and washed in sodium carbonate solution until the carbonate ion exchange is completed, and finally a formed porous composite adsorbent sample is obtained.
[0049] Embodiment 1:
[0050] First, the D290 resin particles were washed with sodium carbonate solution, dilute hydrochloric acid, and ethanol, respectively, then rinsed with deionized water and dried, and then ultrafinely ground and screened to obtain 50-80 μm D290 resin powder. Subsequently, 15 g of LDPE particles were preheated and dissolved in 100 g of diphenyl ether, and 22.5 g of resin powder was added in batches and stirred at high speed to form a uniform casting liquid. The casting liquid was placed in a flat vulcanizer, sandwiched with a polytetrafluoroethylene film, and hot-pressed at 105 ° C and 10 MPa for 5 minutes, and then placed in a 20 ° C cooling bath for rapid cooling and shaping. The obtained membrane was soaked in cyclohexane for 24 hours to extract the diluent, and then repeatedly soaked and washed in a sodium carbonate solution until the carbonate ion exchange was completed, and finally a formed porous composite adsorbent sample was obtained, which can be recorded as D290 / LDPE-1, with a maximum tensile stress of 1.0 MPa and a tensile strain (displacement) of 57%.
[0051] The molding material obtained in Example 1 was subjected to an air concentration CO2 adsorption test at 20°C and 5ppt water vapor partial pressure, and compared with the results obtained by the traditional hot pressing method in Comparative Example 1. The results are shown in Table 1, indicating that the material prepared by hot plate vulcanization according to the present invention has higher adsorption capacity and kinetic properties.
[0052] Table 1
[0053]
[0054] Figure 1 This is the infrared spectrum of the material prepared by hot plate vulcanization in Example 1. From the scanning results, it can be seen that at 2915 cm -1 and 718cm -1 The band has obvious characteristic peaks, which are caused by the typical CH stretching vibration in the benzene ring structure of polystyrene resin. -1 With 1460cm -1 The characteristic peaks at 1630 cm correspond to the NX stretching vibration and the CN stretching vibration. Combining the above, we can see that the quaternary ammonium resin as the active component has been well combined with the engineering plastic carrier, and the -1 The vibration peak caused by C=O indicates that HCO3 has been formed in the adsorbent material after ion exchange treatment. - The material has the ability to absorb ultra-low concentrations of CO2 from the air.
[0055] Figure 2 , Figure 3 Table 2 is a comparison of the SEM characterization and BET results of the materials prepared in Comparative Example 1 and Example 1. The material prepared by hot plate vulcanization in Example 1 is obviously more loosely dispersed in pore structure, and the pore structure in the organic continuous phase left by the diluent serving as both a solvent and a porogen when extracted is more uniform.
[0056] Table 2
[0057]
[0058] Embodiment 2:
[0059] The only difference from Example 1 is that HDPE of the same mass is used to replace LDPE, and the rest are the same to obtain a formed porous composite adsorbent sample.
[0060] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.52 mmol / g, and the half adsorption time was 32 min.
[0061] Embodiment 3:
[0062] The only difference from Example 1 is that LLDPE of the same mass is used to replace LDPE, and the rest are the same to obtain a formed porous composite adsorbent sample.
[0063] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.81 mmol / g, and the half adsorption time was 27 min.
[0064] Embodiment 4:
[0065] The only difference from Example 1 is that the cooling bath temperature used is 0° C., and the rest is the same to obtain a formed porous composite adsorbent sample.
[0066] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.71 mmol / g, and the half adsorption time was 29 min.
[0067] Embodiment 5:
[0068] The only difference from Example 1 is that the cooling bath temperature used is 40° C., and the rest is the same, to obtain a formed porous composite adsorbent sample.
[0069] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.84 mmol / g, and the half adsorption time was 24 min.
[0070] Embodiment 6:
[0071] The only difference from Example 1 is that the cooling bath temperature used is 60° C., and the rest is the same, to obtain a formed porous composite adsorbent sample.
[0072] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.82 mmol / g, and the half adsorption time was 23 min.
[0073] Embodiment 7:
[0074] The only difference from Example 1 is that ethanol of the same mass is used as the extractant instead of cyclohexane, and the rest is the same to obtain a formed porous composite adsorbent sample.
[0075] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.82 mmol / g, and the half adsorption time was 22 min.
[0076] Embodiment 8:
[0077] The only difference from Example 1 is that the same mass of methanol is used as the extractant instead of cyclohexane, and the rest is the same to obtain a formed porous composite adsorbent sample.
[0078] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.91 mmol / g, and the half adsorption time was 18 min.
[0079] Embodiment 9:
[0080] The blank control group differs from Example 1 only in that deionized water is used instead of sodium carbonate solution for ion exchange treatment, and the rest are the same to obtain a formed porous composite adsorbent sample.
[0081] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.02 mmol / g.
[0082] Embodiment 10:
[0083] The only difference from Example 1 is that paraffin oil of the same mass is used as the diluent instead of diphenyl ether, and the rest is the same to obtain a formed porous composite adsorbent sample.
[0084] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.42 mmol / g, and the half adsorption time was 41 min.
[0085] In addition, the molding material obtained in this example was prone to fall apart and had a poor mechanical structure.
[0086] Embodiment 11:
[0087] The only difference from Example 1 is that the same mass of xylene is used as the diluent instead of diphenyl ether, and the rest is the same to obtain a formed porous composite adsorbent sample.
[0088] The porous composite adsorption material obtained in this example was subjected to an air concentration CO2 adsorption test at 20°C and 5 ppt water vapor partial pressure, and the saturated adsorption capacity of the adsorption material was found to be 0.87 mmol / g, and the half adsorption time was 25 min.
[0089] In addition, the molding material obtained in this embodiment has the problems of high volatility and high toxicity.
[0090] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a hot flat plate sulfurized phase separation molded adsorbent suitable for ultra-low concentration carbon dioxide capture, characterized in that: include: Preheating the diluent, adding an inert carrier, dissolving to form a uniform solution, and then adding the active adsorption component and mixing to form a casting solution; The casting liquid is placed on a vulcanized plate, hot pressed, then taken out and placed in a cooling bath to cool and set, the obtained membrane is soaked in an extractant to remove the diluent, and finally the membrane is soaked in a carbonate solution until the ion exchange is completed to obtain an adsorbent.
2. The preparation method according to claim 1, characterized in that: The diluent includes at least one of diphenyl ether, paraffin oil, toluene and xylene; The preheating temperature of the diluent is 90~150℃; The inert carrier includes at least one of low-density polyethylene, linear low-density polyethylene, and high-density polyethylene; The melting point of the low-density polyethylene is 105-115°C; The melting point of the linear low-density polyethylene is 115-125°C; The melting point of the high-density polyethylene is 130-137°C.
3. The preparation method according to claim 1, characterized in that: The active adsorption component includes an active adsorption resin, and the active adsorption resin includes at least one of D290 series, D201 series, D202 series, IRA-900 series macroporous resin, 201*7 series, and HPR4800CL gel-type anion exchange resin; The active adsorption component is washed with a pretreatment solvent and then dried before use; the pretreatment solvent includes at least one of deionized water, sodium carbonate solution, sodium hydroxide solution, hydrochloric acid solution, and ethanol; The active adsorption component is added in the form of particles; the particle size of the active adsorption component particles is 30 to 200 microns, preferably 50 to 80 microns; The time for adding the active adsorption components and mixing is 4 to 8 hours.
4. The preparation method according to claim 1, characterized in that: Taking the mass of the diluent as 100%, the mass of the inert carrier accounts for 10% to 15%, and the mass of the active adsorption component accounts for 20% to 25%.
5. The preparation method according to claim 1, characterized in that: Additive components are also added to the casting solution; Taking the mass of the diluent as 100%, the mass of the additive component accounts for 5% to 15%; The additive component includes one or more of an antioxidant component, a hydrophobic functional additive, and an antistatic additive; The antioxidant component includes at least one of tetrakis(methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)methane and tris(2,4-di-tert-butylphenyl)phosphite; The hydrophobic functional additive includes at least one of polyvinylidene fluoride and polyvinyl fluoride; the weight average molecular weight of the polyvinylidene fluoride is 180000-534000 g / mol; the number average molecular weight of the polyvinyl fluoride is 50000-120000 g / mol; The antistatic additive includes at least one of N,N-bis(2-hydroxyethyl)-N-(3′-dodecyloxy-2′-hydroxypropyl)methylammonium methyl sulfate and stearyltrimethylammonium chloride.
6. The preparation method according to claim 1, characterized in that: The temperature of the hot pressing is 80-130°C; The hot pressing pressure is 4 to 20 MPa; The heat pressing time is 5 to 60 minutes; The temperature of the cooling bath is 0 to 60°C, preferably 10 to 30°C, more preferably 15 to 25°C, and even more preferably 20°C; The thickness of the diaphragm is 0.2 to 2 mm; The extractant includes at least one of ethanol, methanol and cyclohexane.
7. The adsorbent prepared according to the preparation method according to any one of claims 1 to 6.
8. The adsorbent according to claim 7, characterized in that The BET specific surface area of the adsorbent is greater than 9 m 2 / g, porosity greater than 60%, total pore volume greater than 0.5cm 3 / g.
9. Use of the adsorbent according to claim 7 or 8 in capturing carbon dioxide.
10. The use according to claim 9, characterized in that: The adsorbent is used for direct capture of carbon dioxide from air.
Citation Information
Patent Citations
Hydrophobic quaternary ammonium polymer adsorbent suitable for trapping ultralow-concentration carbon dioxide as well as preparation and application of hydrophobic quaternary ammonium polymer adsorbent
CN116422302A
Thin-layer composite ionic liquid supported liquid membrane as well as continuous preparation method and application thereof
CN117258565A
Molding and purifying material for capturing CO2 in air and preparation method of molding and purifying material
CN118847060A
Raw material solution for preparing membrane, porous membrane, and method for preparing porous membrane
JP2008062227A
Method for producing carbon dioxide separation membrane, resin composition for carbon dioxide separation membrane, carbon dioxide separation membrane module, and apparatus for separating carbon dioxide
JP2016117045A
